2018
DOI: 10.1080/16549716.2018.1520473
|View full text |Cite
|
Sign up to set email alerts
|

Time to anti-retroviral therapy among people living with HIV enrolled into care in Myanmar: how prepared are we for ‘test and treat’?

Abstract: Background: Among people living with HIV (PLHIV) enrolled into care, time to anti-retroviral therapy (ART) has not been studied in Myanmar. To inform progress, we conducted this operational research among treatment-naive PLHIV (≥18 years) enrolled during a period of three years (2014–2016) at Pyin Oo Lwin, Myanmar. Objectives: To determine (i) the time from HIV diagnosis to ART initiation (time to ART) and associated factors and (ii) the association between time to ART and attrition (loss to follow-up and deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…The overall linkage to care in our study was within 7 days from HIV diagnosis in 54.0% and within 30 days in 86.0%, which is higher than reported in some other studies 20 , 24 , 25 . Still, the question on how quickly ART should be initiated after the confirmed or even suspected HIV diagnosis has been of major focus in recent years.…”
Section: Discussioncontrasting
confidence: 71%
“…The overall linkage to care in our study was within 7 days from HIV diagnosis in 54.0% and within 30 days in 86.0%, which is higher than reported in some other studies 20 , 24 , 25 . Still, the question on how quickly ART should be initiated after the confirmed or even suspected HIV diagnosis has been of major focus in recent years.…”
Section: Discussioncontrasting
confidence: 71%
“…39 This study also revealed that the hazard of initiating ART as early as possible was shorter in females, urban dwellers, and individuals with baseline OIs when compared with their counterparts of male, rural dwellers, and those without baseline OIs. This finding is supported by study findings from Myanmar, South Africa, and Ekurhuleni; 32,40,41 the reason why females initiated ART earlier than men may be attributed to conditions such as being pregnant, lactating and in labor and delivery, during which they are tested for HIV, and the providers strictly advise them to initiate the therapy early to prevent mother to child HIV transmission. Thus, the women may accept the advice and try to minimize the probability of infecting her neonate through placenta, labor/delivery and breast feeding and are then enforced to take ART earlier.…”
mentioning
confidence: 55%
“…This result is in line with study results from Kampala, Uganda that reported the median time to ART initiation was 6 days, 8 and review of evidence regarding rapid ART initiation, which revealed that newly diagnosed HIV-positive individuals on average started ART within 7 days of a confirmed positive HIV diagnosis. 37 However, this is shorter than in study results conducted in Myanmar, 32 Croatia, 38 and Melbourne, Australia 39 which reported the median time to ART initiation as of 29, 30, and 77 days respectively. The variation may be due to the different criteria used to initiate ART for newly diagnosed HIV-positive individuals.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Regarding ART provision, after HIV status was confirmed patients were enrolled and assessed for eligibility for ART initiation. If patients were eligible ART were started otherwise Pre-ART care would be provided 15 . Coverage of ART substantially increases from 25% in 2012 to 49% in 2015 and 66% in 2017 11 .…”
Section: Research Articlementioning
confidence: 99%